Icing Management on the Veterans' Glass City Skyway Stay Cables. Issue 1 (January 2015) - Mirto, Clinton; Abdelaal, Ahmed; Nims, Douglas; Ng, Tsun-Ming; Hunt, Victor; Helmicki, Arthur; Ryerson, Charles; Jones, Kathleen
Ice falling from the stay sheaths of a cable-stayed bridge is fairly uncommon. However, this problem may potentially affect the majority of cable-stayed bridges in the United States, because more than 80% of them are located in or near areas that have had historically damaging ice storms. This paper offers insight into the overall stay sheath icing problem and provides specific details. The Veterans' Glass City Skyway (VGCS) has had five major icing events since its opening in 2007. This paper discusses the history of the VGCS icing events, weather conditions leading to stay icing, active and passive anti-icing and deicing technologies that were assessed, technologies that were considered potentially practical, tests of those technologies, and novel technologies that were developed to improve icing management. Ultimately, the testing and evaluation showed that no existing technology met the needs of the Ohio Department of Transportation (DOT). Therefore, the Ohio DOT elected to pursue an administrative strategy. To do this effectively requires an understanding of the regional climate, the microclimate on the bridge, and the conditions of the stays. The necessary information was gleaned from existing weather stations, the roadway information system, and new dedicated sensors mounted on the bridge. The weather history and current conditions of the stays were integrated through an automated real-time monitoring system to provide actionable information to the bridge operators.